THE INFLUENCES OF FACEBOOK ON HIGH SCHOOL STUDENTS’ PATTERN OF SOCIAL LIFE: THE CASE OF HARAR CITY - Shoa, Dame Dereba; Keno, Gutema Imana (The Journal of Society and Media, 2020)
In today?s world, it seems that social media and youngsters are destined for each other as both are young, fast paced and ever changing. It has become very challenging to cultivate and socialize youngsters with patterned social norms due to the influences of media like television and Facebook. Educators are challenged more seriously than ever before to teach youngster, as students are using Facebook at school and home. The aim of this study was to investigate the multifaceted influences of Facebook on youth's pattern of social life. Both quantitative and qualitative methods of data collection were employed to collect the data. Questionnaire, interview schedule and key informant interviews were data collection tools used to collect the quatitative and qualitative data respectively. The study founded that, Facebook is a social medium that discourages social bond in one way and encourages in the other way. By networking peers online, it enhances strong affiliation among Facebook friends while by letting them ignore people who are nearby, it debilitates face to face to face personal interactions. Anonymous Facebook users can meet in ?chat rooms? and discuss on topics of their choices with the person they do not know before and this type of electronic friendship and interaction may grow up and leads to virtual physical face-to-face contacts. Facebook is therefore, a platform for youths to discuss and interact on the issues of mutual curiosity which could enhance and promote synchronization of friends on the one side and inflammatory rhetoric conflicts on the other side, which implies the inevitable and multidimensional influences of Facebook on the youth?s social life